EDGARITE, FENB3S6, FIRST NATURAL NIOBIUM-RICH SULFIDE FROM THE KHIBINA ALKALINE COMPLEX, RUSSIAN FAR NORTH: EVIDENCE FOR CHALCOPHILE BEHAVIOR OF NB IN A FENITE - Barkov A.Y.; Martin R.F.; Men'shikov Y.P.; Savchenko Y.E.; Thibault Y.; Laajoki K.V.O. (My University, 2000)
The new mineral species edgarite, FeNb3S6, was discovered in a feldspar-rich fenite, in a fenitized xenolith enclosed by nepheline syenite of the Khibina alkaline complex, Kola Peninsula, northwestern Russia. It occurs as platy inclusions (up to 0.15 mm) in Ti-(V)-rich pyrrhotite and ferroan alabandite, and as dark gray aggregates of platy grains located on the surface of the pyrrhotite. The associated minerals include Ti-(V)-rich marcasite, Mn-Fe-rich wurtzite-2H, corundum, nearly end member phlogopite, rutile, monazite-(Ce), and a graphite-like material. Edgarite is soft (VHN5;10= 135-205 kg/mm2), distinctly bireflectant, and has a strong anisotropy. Its reflectance in air (and in oil) (R1 and R2 in percent, respectively) is: 470 nm: 28.1, 40.2 (13.0, 24.2), 546 nm: 27.4, 39.3 (12.3, 22.7), 589 nm: 27.0, 38.5 (12.2, 21.7), and 650 nm: 27.0, 36.9 (12.4, 20.3). The composition is Nb 52.87, Fe 10.12, V 0.36, Mn 0.10, Ti 0.04, S 35.86, sum 99.35 wt%, which corresponds to (Fe0.96V0.04Mn0.01)Σ1.01Nb3.03S5.95 (basis: Σ atoms=10). By analogy with synthetic FeNb3S6, the X-ray powder pattern of edgarite was indexed on a hexagonal cell, a=5.771(1), c=12.190(6) A, and V=351.6(3) A3, Dcalc is 4.99 g/cm3. The space group is most probably P6322, with Z=2. The strongest lines of the pattern [d in A (I, hkl)] are: 6.11 (8, 002), 3.04 (6, 004), 2.88 (5, 110), 2.606 (8, 112), 2.096 (10, 114), 1.665 (8, 300), 1.524 (6, 008), 1.126 (7, 322), and 1.027 (6, 414). Edgarite appears to have formed at a very late or final stage of metasomatism, after the main event of fenitization, from a highly reduced, subalkaline S-C-H-rich fluid, which may have remobilized Nb as a result of destabilization of oxide minerals. These reducing conditions promoted the chalcophile behavior of lithophile elements (Nb, Ti, V and Mn) on a local scale in the fenite.